Study on Anatomical Variations of Popliteal Artery and its Branches - Reema Kanchan Khalkho; A. K. Dubey; Prasad, Renu; Lal, Prabhat Kumar (Academia Anatomica International, 2020)
Introduction: Variations in branching of popliteal artery is important for the orthopaedicians, vascular surgeons and radiologists. The present study was conducted to assess the anatomical variations in popliteal artery, its terminal branching pattern. Subjects and Methods: The present cross-sectional study included 72 lower limbs received for cadaveric dissection. Anatomical variations of the popliteal artery were noted. Results: Type IA was the most common pattern seen (87.5%) followed by IB (5.6%) and IC (2.8%). One each of types IIA2, IIB and IIC were also seen. Mean length of 162.1 7.9 mm was observed from adductor magnus to the bifurcation point of popliteal artery. Conclusion: Type IA was the most common branching pattern seen in this area. However, types IB, IC, IIA2, IIB and IIC were also seen.